Pengaruh Model Pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) terhadap Kemampuan Koneksi Matematis Siswa di SMP Negeri 206 Jakarta: Pengaruh Model Pembelajaran CORE - Nugroho, Sigit Galih (Jurnal Riset Pendidikan Matematika Jakarta, 2020)
This study aims to determine whether there is a significant effect of the application of the CORE learning model (Connecting, Organizing, Reflecting, Extending) on ​​students' mathematical connection abilities. This research was conducted on eighth grade students at SMP Negeri 206 Jakarta in the even semester of the 2019/2020 academic year on Pythagorean material. The research method used is a quasi-experimental design (quasi-experimental). Sampling using simple random sampling technique. The simple random sampling technique is carried out by randomly selecting two of the four classes that are normally distributed, homogeneous, and have the same average to serve as the experimental class (CORE learning model (Connecting, Organizing, Reflecting, Extending)) and the control class (conventional learning model). The research instrument used was a mathematical connection ability test on the Pythagorean material as many as 4 description questions. Before being used, the instrument has been tested for content validity, construct validity, and empirical validity. The reliability calculation was carried out using the Cronbach Alpha formula and obtained a reliability coefficient of r_11 = 0.798 which was included in the high category. Based on the calculation of the research data, the data for the two classes came from a normally distributed population and had the same or homogeneous variance. Therefore, statistical hypothesis testing was carried out using t-test statistics with the same variance. Based on the results of hypothesis testing, the value of 1.745> 1.668, which means rejecting H0 at a significance level of = 0.05. Thus, it can be concluded that there is a significant effect of the CORE (Connecting, Organizing, Reflecting, Extending) learning model on the mathematical connection abilities of students at SMP Negeri 206 Jakarta on Pythagorean material with a significance level of = 0.05.